A comparison between different foaming methods for the synthesis of light weight geopolymers - Masi, G.; Rickard, William; Vickers, Les; Bignozzi, M.; Van Riessen, Arie (Elsevier Science Ltd, 2014)
Foaming to reduce the density of geopolymeric materials is increasingly being reported in the literature as it has been shown to be effective in improving their insulating properties. However, there is no consistency in foaming methods and as such this study was performed to compare methods in order to better understand their effect on the properties of geopolymers. A surfactant and two chemical foaming agents (hydrogen peroxide and aluminium powder) were added to a fly ash based geopolymer matrix. Surfactant was also combined with each of the chemical foaming agents in order to stabilise the foam in the geopolymer matrix and to reduce coarse pores. The physical, mechanical and microstructural properties of the low density geopolymers are presented and the effects of the foaming agents’ characteristics on the hardened product is discussed, as well as the relative merits of the different procedures to synthesise the foamed geopolymer. It was found that homogeneous microstructures with small pores can be obtained by adding surfactant and hydrogen peroxide. The combination of hydrogen peroxide (0.1 wt%) and surfactant (1.0 wt%) produced geopolymer foams with density and compressive strength values of 0.94 g/cm3 and 4.6 MPa, respectively.